Pengaruh Manajemen Sumber Daya Manusia dan Lingkungan Kerja terhadap Produktivitas Kerja dalam Proyek Pemeliharaan Gedung Bandara Kualanamu pada PT Karya Vany Konstruksi Sumatera Utara - Febriyanti Silitonga; Tohap Parulian Sihombing (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to determine the effect of human resource management and work environment on work productivity in the Kualanamu Airport building maintenance project at PT Karya Vany Konstruksi Sumatera Utara. Human resource management and work environment are important factors that can affect employee work productivity in project implementation. This research was conducted by distributing questionnaires to employees directly involved in the building maintenance project. The results of the study indicate that good human resource management and a comfortable and safe work environment can increase employee productivity. Therefore, the company is expected to pay attention to human resource management and work environment conditions so that work productivity can continue to be improved. In addition, effective communication between management and employees also plays an important role in supporting the achievement of project objectives. Employees who receive clear direction, appropriate supervision, and adequate support from management tend to demonstrate higher levels of motivation and responsibility in completing their tasks. A conducive work environment not only improves physical comfort but also contributes to employees’ psychological well-being, which ultimately affects their performance and efficiency at work. The findings of this study are expected to provide useful insights for companies in developing better management strategies and creating a more supportive work environment. Furthermore, this research can serve as a reference for future studies related to human resource management, work environment, and employee productivity in the construction sector.